Effects of work-family conflict, social support and burnout on job satisfaction among primary care physicians in Huaihai economic zone - Wen, Zongliang; Wu, Shenqin; Bai, Long; Jintao, Xu; Zhao, Yun; Fang, Jinhua; Abdirizak Jama, Hamdi (Frontiers in Psychiatry, 2024)
Background: Primary care physicians (PCPs) are doctors in primary health care institutions, namely village clinics, township health centers and community health service centers (stations) who are the main providers of primary health care services in primary health care settings. Improving the overall health status of the population requires the support of a large number of primary care physicians; however, the job satisfaction of this group has not been sufficiently emphasized and recognized.Objective: The purpose of this study was to examine the effects of primary care physicians' workfamily conflict on their job satisfaction, as well as the mediating role of burnout and the moderating role of social support.Methods: This cross-sectional study was conducted from February 2023 to March 2023. Participants were 749 primary care physicians from four cities of Xuzhou, Linyi, Huaibei, and Shangqiu in the Huaihai Economic Zone of China. SPSS statistical analysis was used to evaluate the relationship between work-family conflict, social support, burnout and job satisfaction among medical workers.Results: Work-family conflict had a significant negative effect on job satisfaction (β = -0.36, p< 0.001), after adding burnout in the model, work-family conflict also negatively predicted job satisfaction (β = -0.32, p< 0.001). Social support had a moderating effect on the direct effect of burnout on job satisfaction (β = 0.00, t = 2.66, p< 0.01, 95%CI [0.001, 0.007]), the predictive effect of burnout on job satisfaction at high level of social support (β = -0.45, p< 0.001) was higher than a low level of social support (β = -0.33, p< 0.001). Conclusions: This study demonstrated the negative impact of work-family conflict on primary care physicians' job satisfaction, as well as the mediating role of burnout and the moderating role of social support on burnout and job satisfaction, which are important for improving primary care physicians' job satisfaction and enhancing the quality of primary care in the future.